The big picture - Rhoades, Jason; Rugoff, Ralph; McCarthy, Paul; Meyer-Hermann, Eva (Zurich : JRP/Ringier, 2012)
The publication focuses in part on Rhoades' installation "Perfect world" which was created for the Deichtorhallen Hamburg, 1999 and "1:12 Perfect world" which was shown at Hauser & Wirth, 2010.
kunstcatalogus
Keywords: Rhoades, Jason